Recommendations for the Design of Serious Games in Neurodegenerative Diseases - Ben-Sadoun, Grégory; Manera, Valeria; Alvarez, Julian; Sacco, Guillaume; Robert, Philippe (Frontiers in Aging Neuroscience, 2018)
The use of Serious Games (SG) in the health domain is expanding. In the field of Neurodegenerative Diseases (ND) such as Alzheimer’s Disease, SG are currently employed to provide alternative solutions for patients’ treatment, stimulation, and rehabilitation. The design of SG for people with ND implies collaborations between professionals in ND and professionals in SG design. As the field is quite young, professionals specialized in both ND and SG are still rare, and recommendations for the design of SG for people with ND are still missing. This perspective paper aims to provide recommendations in terms of ergonomic choices for the design of SG aiming at stimulating people with ND, starting from the existing SG already tested in this population: “MINWii”, “Kitchen and Cooking” and “X-Torp”. We propose to rely on nine ergonomic criteria: eight ergonomic criteria inspired by works in the domain of office automation: Compatibility, Guidance, Workload, Adaptability, Consistency, Significance of codes, Explicit control and Error management; and one ergonomic criterion related to videogame: the game rules. Perspectives derived from this proposal are also discussed.